Characterization of A Baculovirus of Spodoptera litura (Lepidoptera : Noctuidae) Isolated from Yogyakarta - Arman Wijonarko; Sedyo Hartono; Tri Harjaka; Nuri Yusmarlita (Jurnal Perlindungan Tanaman Indonesia, 2007)
A Baculovirus has been isolated from cadaver of larvae of Spodoptera litura, a Noctuidae of agricultural pest, importance due to its wide-range hosts and the damage to their respective host. Phase contrast light microscopy observation from infected larvae showed that the fat body, hemocyte cells, and cells surrounding the trachea or tracheolus were the most tissue invaded by polyhedra. Transmission electron microscopy analysis of the occlusion body purified from diseased larva showed that the baculovirus envelope containing multiple nucleocapsid. Digestion of viral DNA with three restriction enzymes showed that the genome pattern of baculovirus isolated from Bantul were close to SpliNPV isolated from Japan and those of Spodoptera littoralis and quite distinct from those isolated from Southeast Asia region. Bioassay test performed on first to fifth instar larvae showed that the virus effectively control the young larvae, but showed some level of resistance against older larvae of Spodoptera litura.